10.1016/s0029-7437(07)70549-9 (CrossRef Listing of Deleted DOIs, 2000)
AIM: Meconium-related ileus (MRI) often mimics other surgical pathologies in extremely low birth weight infants (ELBWIs), leading to diagnostic difficulties. This study aimed to clarify the clinical presentation and management outcomes of enema therapy in ELBWIs with a specific focus on the clinical indicators of underlying non-MRI surgical pathologies. METHODS: A retrospective review was conducted of 31 ELBWIs (birth weight < 1000 g) who received enema therapy for suspected MRI at a single tertiary center between 2008 and 2024. Infants were categorized into Success (n = 20) and Failure (n = 11) groups. The clinical characteristics, timing of intervention, and underlying pathologies were compared. RESULTS: Underlying non-MRI surgical pathologies were identified only in the Failure group (36% [4/11] vs. 0% [0/20] in the Success group, p = 0.010), including Hirschsprung disease, necrotizing enterocolitis, meconium peritonitis, and ileal stenosis. The overall survival was significantly lower in the Failure group than in the Success group (55% vs. 95%, p = 0.013). A descriptive review of these non-MRI patients highlighted that an atypically late initial enema therapy or a high frequency of repetitive procedures was critical clinical features that masked the underlying pathologies. CONCLUSION: In ELBWIs with suspected MRI, the failure of enema therapy was significantly associated with underlying non-MRI surgical pathologies. Although these findings require validation in larger cohorts, delayed initiation of therapeutic enema or repeated procedures without sustained improvement should prompt reassessment for non-MRI surgical pathology and early surgical consultation.